Evaluation of effects of Forsus Fatigue Resistance device in correction of class II division 1 malocclusion in adolescent patient: A case report - Anupama V Jain; Anand K Patil; Roopak Naik (Journal of Dental Problems and Solutions - Peertechz Publications, 2022)
Introduction: Class II malocclusion is one of the most prevalent malocclusions. The Class II malocclusions are caused due to forwardly placed maxilla, the backward position of the mandible, or a combination of both these factors. This disparity in skeletal base growth and position can be corrected during growth spurts using functional and fixed functional appliances. Description: An adolescent boy with Class II division 1 malocclusion, retrusive mandible, and increased overjet was treated with a pre-adjusted edgewise appliance (0.022-slot Gemini 3M -MBT prescription) along with a fixed functional appliance, Forsus TM Fatigue Resistant Device. The Skeletal age of the patient assessment using Hand wrist radiograph and CVM showed a major part of the adolescent growth spurt to be completed. Pre-treatment and post-functional cephalograms were traced and superimposed to compare changes in the skeletal base and dental structures. Result: The Class II molar and canine relationships were corrected to class I and the mandible showed forward positioning leading to correction for the skeletal base to class I. The facial profile showed marked improvement to an orthognathic pleasing profile. Conclusion: The purpose of this case report is to emphasize on use of fixed functional appliances in the treatment of adolescents with skeletal base discrepancies like Class II division 1 malocclusion. Intervention with fixed functional appliances at the appropriate skeletal age can prevent the need for extractions or other surgical procedures that may be needed to correct the malocclusion.